Angiotensin II receptor blockers in modulation of transforming growth factor-beta effects on mitral valve myxomatous degeneration. (14th October 2021) - Malev, E; Omelchenko, M; Mitrofanova, L; Konovalov, P; Reeva, S; Timofeev, E
Abstract: : Growing evidence supports role transforming growth factor-β (TGF-β) as a mediator of the myxomatous changes in the mitral valve prolapse. Recently, angiotensin II receptor blockers (ARB) emerged as a potentially effective inhibitor of TGF-β signaling. Treatment of valvular interstitial cells (VICs) with ARB resulted in effective inhibition of TGF-β-induced ECM expression. Our aim was to evaluate the effect of preoperative ARB therapy in modulation of transforming growth factor-β effects on mitral valve myxomatous degeneration. Methods: A total of 233 asymptomatic patients (mean age: 53.8±12.9) undergoing mitral valve surgery for severe mitral regurgitation due to mitral valve prolapse were enrolled in our retrospective, non-randomized, single-center study. Resected abnormal segments of the mitral leaflets (segment of the posterior leaflet or the entire valve) were obtained during mitral valve repair/replacement surgery and examined by experienced pathologists. Immunohistochemical characterization of mitral valve sections was performed with the primary antibodies. Quantification was performed by counting TGF-β1 and TGF-β2 positive cells within 10 random high-power fields divided by the total number of cells in specimens. Quantification of immunohistochemical staining for collagen III was performed by measurement of staining area divided by the total area of the specimens. Results: Two hundred thirty-three consecutive patients (66% males, mean age 53.8±12.9 years, range 19–80) with severe MR were enrolled in the study. According to the case reports, 43 patients (18.5%) received losartan or telmisartan before surgery and were included in study group. 190 patients (81.5%) did not receive any ARB and were enrolled in the control group. Histological examination showed disorganized collagen and elastin fibers, expansion of the spongiosa layer in both groups. However, MV specimens' immunohistochemistry revealed a lower expression of type III collagen in ARB group as compared to controls (31.3% ± 10.8% vs. 43.8% ± 15.3%; p<0.001). MV leaflets in control group showed the increased VICs density (95.3±39.9 vs. 70.0±21.7/high-power field, p=0.0001). TGF-β1 and TGF-β2 positive cells were significantly rare in the ARB than in control MV specimens (18% vs. 33%, p=0.012 and 16% vs. 38%, p<0.ehab724.15541, respectively). Expression of type III collagen and TGF-β2 positive cells count showed a weak, but significant correlation (r=0.28; p=0.ehab724.155414). The multivariate Cox analysis showed a decrease in the relative risk of valvular thickening (myxomatous degeneration) with ARB therapy (0.85; 95% CI: 0.61 – 1.17; p=0.01). Conclusions: We indicate a beneficial effect of ARB treatment through the inhibition of TGF-β pathway on valvular myxomatous degeneration in patients with MVP. Modulation of the progression of MVP with such therapeutic agents may have great clinical significance. FUNDunding Acknowledgement: Type of funding sources: None.